Intrauterine insulin resistance in fetuses of overweight mothers. Issue 1 (13th June 2012) - Liu, Bin; Xu, Yun; Liang, Jian‐ming; Voss, Courtney; Xiao, Huan‐yu; Sheng, Wei‐yang; Sun, Yan‐hong; Wang, Zi‐lian
Abstract Aim: To investigate the relationship between maternal overweight and fetal insulin resistance. Material and Methods: Nineteen overweight and 30 lean pregnant women were recruited in the present study. Maternal and fetal insulin resistance were determined by measuring sex hormone binding globulin (SHBG) concentrations in maternal venous or umbilical cord serum, respectively. Maternal age, gestational age, height, pre‐gravidity weight, pre‐partum weight, as well as fetal gender, birth weight, birth height, and head circumference were collected as clinical data. Results: Fetuses of overweight mothers had larger birth weight (3.58 ± 0.55 kg vs 3.32 ± 0.42, adjusted P = 0.006) and lower SHBG concentrations (26.64 ± 3.65 vs 34.36 ± 7.84, adjusted P = 0.007) than those of lean mothers after values were adjusted for potential cofactors. Fetal SHBG level was negatively correlated with pre‐gravidity body mass index (R = −0.392, adjusted P = 0.025) and weight gain during pregnancy (R = −0.332, adjusted P = 0.026) even with adjustment for potential cofactors. Among the 29 pregnant women with gestational diabetes mellitus, the overweight mothers had higher H1AC levels than their lean counterparts (6.47 ± 0.44 vs 5.74 ± 0.52, adjusted P = 0.004). Conclusion: Intrauterine insulin resistance is more prominent in fetuses of overweight mothers, an effect that is decreased by weight gain control during pregnancy.